An investigation on the continuous and uniform thin membrane passive film formed on sputtered nanocrystalline stainless steel. (March 2016) - Li, Tianshu; Liu, Li; Zhang, Bin; Li, Ying; Wang, Fuhui
Highlights: The thin membrane passive film on the NCss was directly observed. The passive film presented a distinctly duplex layer with an amorphous structure. The nanostructure and homogenous composition improve the passive film performance. The critical pitting temperature of the NCss was a relatively random transition. Abstract: The thin membrane passive film on the sputtered nanocrystalline stainless steel was directly observed. The passive film was very uniform, continuous and showed a distinctly double-layered structure. The formation of such a protective passive film was mainly attributed to the nanocrystalline structure, the homogenous chemical composition and being free of the inclusions. The critical pitting temperature of the sputtered NCss was no longer a deterministic transition, but a relatively random transition with a wide temperature distribution, which was speculated to be governed by surface morphology.